Implementasi Pendidikan Pada Masa Covid-19 Dalam Perspektif Sosiologi - Mutiyati Mutiyati; Yuniarti Yuniarti (Edification Journal : Pendidikan Agama Islam, 2020)
Today the world is shocked by the outbreak of a disease caused by a virus called corona or known as covid-19 (corona virus diseases-19). The virus that began to plague on December 13, 2019 in the city of Wuhan in the Hubei Province of China spread very quickly throughout the world, until March 11, 2020, WHO settled this outbreak as a global pandemic. Hundreds of thousands of people were exposed to this world virus and even dozens of dead victims died. Transmission is very fast and difficult to detect people exposed to because the incubation period of covid-19 for 2 weeks. And transmission occurs because of social activities that can not be avoided. So a lot of impact received from covid-19 and restrictions on social interaction. One of them has an impact on the world of education.This article we will discuss the actions of the government in overcoming the impact of co-19 in the world of education, so that it remains well run and is able to produce young people who have character without the hindrance of learning activities by this co-19 virus outbreak. Pandvid Covid-19 has made the learning system change dramatically from face-to-face meetings to online learners. This study uses a survey method using a questionnaire conducted online. The Tarbiyah and Teacher Training faculties support learning policies at home by implementing online learning.